Cross-Sectoral Collaboration in Empowering Pineapple Farmers: A Case Study of PT Pupuk Kujang's CSR Implementation in the Kampung NanasKu Program - Didin Nahrudin Syah; Ade Cahya Kurniawan; Agung Gustiawan (Prospect Publishing, 2023)
The pineapple commodity is a local product for some residents in West Java, especially in Sarireja Village. This potential needs special attention to maintain local agricultural products. However, the pineapple fruit yields in the Sarireja area were not able to enter the market optimally due to constraints on yields that were less than optimal. Through the assistance of the Kampung Nanasku corporate social responsibility program by promoting the principle of the Tripple Bottom Line, the Kampung Nanasku program is aimed at strengthening the sustainability of the lives of pineapple farmers. The results of this program have been able to provide empowerment to the community in the form of processed pineapple which has added selling value, utilization of pineapple agricultural waste in the form of pineapple leaves which are also used as natural fiber cloth, pineapple skin waste which is integrated with the needs of breeders namely to become feed silage, and pineapple waste rotten to POC.